2011
DOI: 10.3892/etm.2011.387
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of localized, primary gastric diffuse large B-cell lymphoma treated with rituximab and CHOP

Abstract: Abstract. The addition of rituximab to cyclophosphamide, doxorubicin, vincristine and prednisone [CHOP (i.e., R-CHOP)] is considered to be the standard regimen for treating localized, primary gastric diffuse large B-cell lymphoma (PG-DLBCL). However, few studies have reported the long-term efficacy of R-CHOP therapy in the management of localized PG-DLBCL. In the present study, we performed a retrospective analysis of 11 patients with localized PG-DLBCL, who were treated with R-CHOP at Nihon University Itabash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 42 publications
3
6
0
Order By: Relevance
“…In this study, female predominance was documented, which was consistent with reports from Far East countries although literature from western countries reported male predominance (4,5,12,13,(19)(20)(21).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In this study, female predominance was documented, which was consistent with reports from Far East countries although literature from western countries reported male predominance (4,5,12,13,(19)(20)(21).…”
Section: Discussionsupporting
confidence: 80%
“…In only one study on patients at all stages were 5-year OS (100% versus 63.3%) and DFS (100% versus 73.3%) lower in patients treated without rituximab (12). In a study by Kobayashi et al, 5-year OS of 100% was reported in early-stage patients treated with R-CHOP (13). In the light of these findings, there is a discrepancy about the impact of rituximab on OS and DFS in both early-and late-stage diseases.…”
Section: Discussionmentioning
confidence: 98%
“…9,10,13,14,15 Thus, it is very difficult to draw any specific factors that can define a better treatment in this type of neoplasm. PG-DLBCL, at early stage, is generally sensitive to standard chemotherapy, because > 90% can achieve CR; 2,3,11 however, relapse can occur in 20–35%, and in most require aggressive salvage treatments.…”
Section: Discussionmentioning
confidence: 99%
“…1 Actually, the combination of chemotherapy with an anthracycline-based treatment offers the possibility of complete response (CR) in > 90% of patients, with an overall survival (OS) of 76-90% at 5 years. 2,3 Although early stages (I-II) have been considered of good prognosis, a small proportion of cases could have a worse prognosis, and are at risk to relapse, that will need aggressive chemotherapy, including stem cell transplant. However, no specific prognostic factors have been identified including the International Prognostic Index (IPI), because most patients were at low-or low-intermediate clinical risk and will be considered as low risk; other factors such as deep of invasion, tumor burden, lymph node invasion, and molecular profile have not been validated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation